Analisis Molekuler Gen Partenokarpi DefH9-RI-iaaM pada Progeni Tomat Transgenik - Saptowo J Pardal; Slamet Slamet; Ragapadmi Purnamaningsih; Endang G. Lestari; Sutini Sutini (Jurnal AgroBiogen, 2015)
The development of seedless tomato fruits will be more attractive to both consumers and industries. Seedless tomatoes can beproduced through parthenocarpy technology. Artificial parthenocarpy can be induced by conventional crossing, hormoneapplication, or genetic engineering. The development of parthenocarpic tomatoes through genetic engineering has been carriedout by inserting DefH9-iaaM parthenocarpic geneinto tomato genome via Agrobacterium tumefaciens mediated transformation.Sixty putative transgenic tomato lines were produced and three events (OvR1#14-4, OvM2#10-1, and OvM2#6-2) were selectedas the best events. The background of the tomato lines was Oval variety, and based on PCR results, the three selected linescontained DefH9-RI-iaaM in their genome. The objective of this research was to determine the integration of DefH9-RI-iaaMgene in the progenies of three transgenic tomatoes lines using PCR technique. The research was conducted in the laboratoryand Biosafety Containment Facility of Indonesian Center for Agricultural Biotechnology and Genetic Resources Research andDevelopment (ICABIOGRAD). Parental variety, Oval (neither transgenic nor in vitro cultured), and elite line of CL 6046 were usedas control plants. The results indicated that the progenies (T1, T2, and T3) of the three tomato lines contained the insert DefH9-RIiaaMgene.